Accuracy of objective parameters in acute epiglottitis diagnosis: A case–control study. Issue 37 (September 2018) - Kim, Kyung Hee; Kim, Yong Hwan; Lee, Jun Ho; Lee, Dong Woo; Song, Yun Gyu; Cha, Seung Yong; Hwang, Seong Youn
Abstract : Abstract: Lateral neck radiography is often used as a screening tool in emergency departments for suspected acute epiglottitis. The qualitative radiographic signs have been mainly used. The aim of this study was to evaluate the accuracy of objective radiographic parameters to aid diagnosis of acute epiglottitis. Patients who were diagnosed with acute epiglottitis from January 2006 to December 2016 were included in this case–control study. Control subjects with normal lateral neck radiograph findings were included at a 1:4 ratio during the same period. The clinical findings of the patients were assessed from electronic medical records and radiographs were interpreted by a board-certified radiologist and a board-certified emergency medicine physician. The widths of the 3rd cervical vertebral body, epiglottis base (EWB), epiglottis tip (EWT), aryepiglottic fold (AFW), and hypopharynx, as well as the dimensions of the retropharyngeal and retrotracheal soft tissues, were retrospectively measured. The sensitivity, specificity, and receiver operating characteristic (ROC) curves were analyzed for the measured parameters, and cutoff values were determined to predict acute epiglottitis. The predictive cutoff values of radiologic parameters were evaluated using 5-fold cross-validation. A total 260 epiglottitis patients and 1166 controls were included in the study. In the ROC curve analysis, the EWB had an area under the ROC curve (AUROC) of 0.99 for a cutoff value of 5.02 mm (sensitivity, 96.2%; specificity, 98.2%). The EWT had an AUROC of 0.97 for a cutoff value of 4.84 mm (sensitivity, 91.2%; specificity, 97.3%). The AFW had an AUROC of 0.88 for a cutoff value of 6.59 mm (sensitivity, 86.5%; specificity, 78.8%). The 5-fold cross-validation achieved AUROCs of 0.97 for EWB, 0.94 for EWT, and 0.83 for AFW. The objective radiographic parameters in lateral neck radiography may be useful in diagnosing acute epiglottitis. Further prospective studies may be warranted to evaluate the diagnostic performance in actual clinical practice.